Analisis Pemahaman Mahasiswa terhadap Afiksasi dalam Bahasa Indonesia: Studi Kasus di Universitas Negeri Makassar - Herdiani, Rizki; Dewi, Anita Candra; Fitri, Sakinah; Satriani, Irma (HUMAN: South Asian Journal of Social Studies, 2025)
Abstract. The lack of understanding regarding affixation can lead to errors in word usage, resulting in ambiguity in the meaning of their academic writing. This study aims to thoroughly examine how students comprehend affixation in the Indonesian language, the factors influencing that understanding, and the challenges they face in applying it in academic communication. The type of research employed is descriptive qualitative, focusing on the collection and analysis of in-depth data regarding students' understanding of affixation. The sample for this study consists of 68 students from the Indonesian Language and Literature Education programme at Universitas Negeri Makassar. Data collection techniques include interviews, questionnaires, text analysis, and direct classroom observations. Data analysis is conducted through thematic analysis to identify key themes related to the understanding of affixation. The results indicate that the application of affixation in students' academic writing still reveals errors in affix usage, the use of confixes, and the writing of affixes and prepositions. Several factors influencing students' understanding of affixation can be observed from cognitive, pedagogical, and learning environment aspects. Various teaching strategies have proven effective in enhancing students' engagement, conceptual understanding, and analytical skills regarding the structure of affixes in the Indonesian language, including contextual approaches, project-based learning, digital technology, and collaborative methods. This research reinforces the fact that mastery of morphology, particularly affixation, remains a significant challenge in students' academic writing. This necessitates a more applied, contextual, and error-based approach to teaching morphology that addresses the common mistakes encountered.Keywords: affixation, morphology, learning strategies